Analisa Geologi Struktur Lapangan Geothermal Sarulla - Citra Wahyuningrum; Kevin Kevin; Faqqih Badruzzaman (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is a country with great potential geothermal energy resources. Geothermal resources in Sumatra are mostly located along magmatic arcs that correlate with the seismically active Sumatran Fault. One of the unexploited geothermal resources is located around the Tarutung basin, south of Lake Toba, North Sumatra. The presence of an open fracture or fracture correlates very well with depth. Geological structures consisting of faults, lineages, and volcanic features such as tuff-ring structures or maars were identified as a combination of these methods namely Interpretation of topographic maps and satellite imagery (ASTER DEM) and geological mapping and field verification. In the withdrawal of the geological structure of the Sarulla Geothermal Field there are tectonic effects in the form of transpression, transtension and lineation zones. This is due to tectonic activity from the Great Sumatra Fault in its fault zone. The model along the Sarulla basin also consists of three main layers that form the background structure for the shallow graben located in the center.